Lie down with dogs : practice-based development in crime fiction writing : an exegesis presented in partial fulfilment of the requirements for the degree of Master of Creative Enterprise at Massey University, Wellington, New Zealand - Knight, Mathew Sydney (Massey University, 2023)
This project examines the development of the crime fiction novel, Lie Down with Dogs. The novel tells the story of a New Zealand police detective, returning to work after a traumatizing undercover investigation. It uses a non-linear narrative structure, which interweaves three stories from different time periods. Writing this novel within a research context allowed a scholarly analysis from inside the creative development process. The research focussed on two primary aspects. Development structure, examining the methods used to create a full-length novel, and narrative structure, examining the development of the story itself. This project uses practice-based research methodologies which examine the entire creative journey from ideation through to commercialization of the project. The creative practice guided and informed the research, while the research, in turn, informed and contributed to the creative work. The results of these methods are manifest in the creative work and this exegesis. As part of my practice, the commercialization of the creative work is addressed in a separate business pitch deck document looking at the viability of self-publishing the novel utilising digital distribution platforms enabling a direct-to-market pathway for authors.
This Master of Creative Enterprise project comprises an exegesis; a novel, Lie Down With Dogs; and a business plan.
Keywords: 360201 Creative writing (incl. scriptwriting)